Tick-borne Encephalitis Virus in Wild Rodents in Winter, Finland, 2008–2009 - Tonteri, Elina (Centers for Disease Control and Prevention, 2011)
Rodents might maintain tick-borne encephalitis virus (TBEV) in nature through latent persistent infections. During 2 subsequent winters, 2008 and 2009, in Finland, we detected RNA of European and Siberian subtypes of TBEV in Microtus agrestis and Myodes glareolus voles, respectively. Persistence in rodent reservoirs may contribute to virus overwintering.